Blood microbiome and cardiometabolic disease: insights, therapeutic strategies, and future directions - Khan, Ikram; Khan, Imran; Bacha, Ali Sher; Xiaohui, Yu; Xie, Ping; Xie, Xiao-dong; Li, Zhiqiang (Frontiers in Bacteriology, 2025)
Cardiometabolic diseases (CMDs), particularly cardiovascular disease (CVD), type 2 diabetes mellitus (T2DM), and chronic kidney disease (CKD), emerged as primary contributors to global morbidity and mortality. In addition to traditional factors, recent studies demonstrated that blood microbiomes may also promote the development or progression of these CMDs. Traditionally, blood was considered sterile; however, the notion of blood as a sterile environment has been challenged by findings demonstrating the presence of a microbiome in both healthy and disease states. Although there has been a tremendous expansion in human microbiome research, with hundreds of projects underway globally the blood microbiome has not received the same level of attention as its gut and oral counterparts. The circulating microbiome is an emerging trend that has drawn a high level of interest in the biomedical field, given its potential to generate predictive biomarkers and the means to screen for potential pathogens. This comprehensive review explores the latest advancements in blood microbiome research, emphasizing biomarker identification, diagnostic tools, treatment modalities, and prevention in CMDs. We also delve into existing challenges and present a future-oriented treatment strategy using advanced methods. Deciphering the blood microbiome’s role in disease could lead to the classification of patient subgroups, enabling precision microbiota-based therapies.